Rekonstruksionisme Dalam Pendidikan Islam yang Responsif Terhadap Tantangan Zaman - Nurshafitri; Yesha Arista Sulistiawati; Herlini Puspika Sari (4, 2025)
Reconstructionism in Islamic education presents itself as an approach that emphasizes the importance of reforming the education system to be more adaptive to changing times, without neglecting religious values. The challenges of globalization, technological developments, and shifting social values ​​require Islamic education to transform itself to produce a critical, religious, and highly competitive generation. This study aims to examine the potential of reconstructionism as a foundation for building Islamic education that is responsive to contemporary dynamics. Using a qualitative descriptive approach based on literature, data were analyzed through a literature review of various educational theories, the views of Islamic figures, and the realities of modern society. The results of the study indicate that reconstructionism is oriented towards developing critical thinking, upholding social justice, and ecological awareness integrated with Islamic spiritual values. Education is no longer seen merely as the transfer of knowledge, but also as a process of character formation and social awareness. To achieve this, several strategic steps are needed: first, ongoing training for educators to be able to apply the principles of reconstructionism; second, the development of an innovative curriculum that integrates technology and active learning methods; and third, full support from the government through policies, funding, and the provision of resources. With these steps, Islamic education has the potential to produce a generation that excels not only intellectually but also possesses strong social and moral sensitivity. This generation is expected to be agents of change, playing a role in responding to the challenges of the times while upholding Islamic values. Abstrak Rekonstruksionisme dalam pendidikan Islam hadir sebagai sebuah pendekatan yang menekankan pentingnya pembaruan sistem pendidikan agar lebih adaptif terhadap perubahan zaman, tanpa mengabaikan nilai-nilai keagamaan. Tantangan globalisasi, perkembangan teknologi, serta pergeseran nilai sosial menuntut pendidikan Islam untuk bertransformasi sehingga mampu melahirkan generasi yang kritis, religius, dan berdaya saing tinggi. Penelitian ini bertujuan untuk mengkaji potensi rekonstruksionisme sebagai landasan dalam membangun pendidikan Islam yang responsif terhadap dinamika kontemporer. Dengan menggunakan pendekatan deskriptif kualitatif berbasis studi kepustakaan, data dianalisis melalui kajian literatur terhadap berbagai teori pendidikan, pandangan tokoh Islam, serta realitas kebutuhan masyarakat modern. Hasil kajian menunjukkan bahwa rekonstruksionisme berorientasi pada pengembangan pemikiran kritis, penegakan keadilan sosial, dan kesadaran ekologis yang terintegrasi dengan nilai spiritual Islam. Pendidikan tidak lagi dipandang sebatas transfer pengetahuan, tetapi juga proses pembentukan karakter dan kesadaran sosial. Untuk mewujudkan hal tersebut, dibutuhkan beberapa langkah strategis: pertama, pelatihan berkelanjutan bagi pendidik agar mampu menerapkan prinsip rekonstruksionisme; kedua, pengembangan kurikulum inovatif yang mengintegrasikan teknologi serta metode pembelajaran aktif; ketiga, dukungan penuh dari pemerintah melalui kebijakan, pendanaan, dan penyediaan sumber daya. Dengan langkah-langkah tersebut, pendidikan Islam berpotensi melahirkan generasi yang tidak hanya unggul dalam aspek intelektual, tetapi juga memiliki kepekaan sosial dan moral yang kuat. Generasi ini diharapkan mampu menjadi agen perubahan yang berperan dalam menjawab tantangan zaman sekaligus menjaga nilai-nilai keislaman.